Which of the following expressions are not equal to 1?

A) sin^2 theta + cot^2 theta sin^2 theta
B) (sin^2 theta/1-cos theta)-cos theta
C) sec^2 theta + tan^2 theta
D) cot^2 theta sin^2 theta/cos^2theta

Answer: D

1 answer

for D I get
c^2/s^2 * s^2 /c^2 = 1 sorry

A gives
s^2 (1 + c^2/s^2) = s^2 + c^2 = 1

B gives (does not make sense the way you wrote it)
Maybe you mean
sin^2 theta/(1-cos theta)-cos theta
[s^2 -c (1-c)] /(1-c)
[ s^2 + c^2 -c] / (1-c)
(1-c) / (1-c)
1

C gives
(1/c^2) + s^2/c^2
= (1 + s^2)/c^2
not 1